Culture troubles politics and the interpretation of meaning - Chabal, Patrick 1951-2014; Daloz, Jean-Pascal 1960- (Hurst, 2006)
A systematic examination and re-evaluation of the role of culture in political analysis. The authors' contentions are that it is unwise to compare different societies without taking into account culture; a cultural approach contributes to making political comparison meaningful; and that conceptual frameworks can be based on an eclectic approach.
Keywords: Politics and culture; Comparative government; Kultur; Politisches System